Pengaruh Transformasi Digital Terhadap Kinerja Usaha Mikro, Kecil, Dan Menengah (UMKM) Di Indonesia - Mendrofa, Romi Cristians Love; Zebua, Dermawan (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
Digital transformation has become a crucial factor in enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in the digital economy era. The use of digital technologies such as social media, e-commerce, digital payment systems, and business management applications provides opportunities for MSMEs to improve operational efficiency, expand markets, and enhance business performance. This study aims to analyze the impact of digital transformation on the performance of MSMEs in Indonesia through a literature review approach. The research method used is qualitative descriptive analysis by reviewing various relevant scientific journals, books, and official reports. The results show that digital transformation has a positive impact on increasing revenue, cost efficiency, and the competitiveness of MSMEs. However, the implementation of digital transformation still faces various challenges, such as limited digital literacy, technological infrastructure, and human resources. Therefore, support from the government, educational institutions, and the private sector is essential to encourage the success of MSME digital transformation in Indonesia.